2014
DOI: 10.1117/1.nph.1.2.025008
|View full text |Cite
|
Sign up to set email alerts
|

Fast calcium sensor proteins for monitoring neural activity

Abstract: A major goal of the BRAIN Initiative is the development of technologies to monitor neuronal network activity during active information processing. Toward this goal, genetically encoded calcium indicator proteins have become widely used for reporting activity in preparations ranging from invertebrates to awake mammals. However, slow response times, the narrow sensitivity range of Ca2+ and in some cases, poor signal-to-noise ratio still limit their usefulness. Here, we review recent improvements in the field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 84 publications
(111 reference statements)
6
107
1
Order By: Relevance
“…To date, only morphological studies have been reported in chronically imaged cerebellum (Allegra Mascaro et al 2013; Carrillo et al 2013aCarrillo et al , 2013bKuhn et al 2012). Even in cases where acute imaging of a GECI was performed, functional imaging occurred within 14 days of surgery (Badura et al 2014;Kuhn et al 2012;Najafi et al 2014). In this report, we chronically imaged Ca 2ϩ activity in PCs for up to 7 wk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only morphological studies have been reported in chronically imaged cerebellum (Allegra Mascaro et al 2013; Carrillo et al 2013aCarrillo et al , 2013bKuhn et al 2012). Even in cases where acute imaging of a GECI was performed, functional imaging occurred within 14 days of surgery (Badura et al 2014;Kuhn et al 2012;Najafi et al 2014). In this report, we chronically imaged Ca 2ϩ activity in PCs for up to 7 wk.…”
Section: Discussionmentioning
confidence: 99%
“…Genetically encoded Ca 2ϩ indicators (GECIs) provide a solution to problems found with injectable dyes but until recently have not been used in PCs (acutely, Badura et al 2014;Kuhn et al 2012;Najafi et al 2014). The inability to maintain a clear window long enough to image, particularly after viral injections, could account for this scarcity.…”
mentioning
confidence: 99%
“…As a summary, calcium sensitive small molecular dyes have several advantages over GECIs, including faster responses, near-linear responses, and higher sensitivities [22,23]. In contrast, GECIs can be better targeted into specific cell types or specific cell compartments, allow long term measurements, and have better signal to noise ratios at least in in vivo experiments [22].…”
Section: Methods For Studying Calcium Signals In Human Ps Cellsmentioning
confidence: 99%
“…In contrast, GECIs can be better targeted into specific cell types or specific cell compartments, allow long term measurements, and have better signal to noise ratios at least in in vivo experiments [22]. A recent development of GECIs has resulted in a new class of indicator proteins, including GCaMP6, with higher sensitivity and detection reliability even for individual action potentials in neurons [24].…”
Section: Methods For Studying Calcium Signals In Human Ps Cellsmentioning
confidence: 99%
“…• GCamp6f protein for calcium imaging [78,107]. It is the fastest genetically-encoded calcium indicator (for cytoplasmic free calcium) in neurons which makes it very attractive for fast acquisitions.…”
Section: Presentation Of the Optogenetics Systemmentioning
confidence: 99%